Tree diversity drives diversity of arthropod herbivores, but successional stage mediates detritivores. Issue 21 (18th September 2017) - O'Brien, Michael J.; Brezzi, Matteo; Schuldt, Andreas; Zhang, Jia‐Yong; Ma, Keping; Schmid, Bernhard; Niklaus, Pascal A.
Abstract: The high tree diversity of subtropical forests is linked to the biodiversity of other trophic levels. Disentangling the effects of tree species richness and composition, forest age, and stand structure on higher trophic levels in a forest landscape is important for understanding the factors that promote biodiversity and ecosystem functioning. Using a plot network spanning gradients of tree diversity and secondary succession in subtropical forest, we tested the effects of tree community characteristics (species richness and composition) and forest succession (stand age) on arthropod community characteristics (morphotype diversity, abundance and composition) of four arthropod functional groups. We posit that these gradients differentially affect the arthropod functional groups, which mediates the diversity, composition, and abundance of arthropods in subtropical forests. We found that herbivore richness was positively related to tree species richness. Furthermore, the composition of herbivore communities was associated with tree species composition. In contrast, detritivore richness and composition was associated with stand age instead of tree diversity. Predator and pollinator richness and abundance were not strongly related to either gradient, although positive trends with tree species richness were found for predators. The weaker effect of tree diversity on predators suggests a cascading diversity effect from trees to herbivores to predators. Our results suggest that arthropod diversity in a subtropical forest reflects the net outcome of complex interactions among variables associated with tree diversity and stand age. Despite this complexity, there are clear linkages between the overall richness and composition of tree and arthropod communities, in particular herbivores, demonstrating that these trophic levels directly impact each other. Abstract : Using a plot network spanning gradients of tree diversity and secondary succession in subtropical forest, we tested the effect of tree community characteristics (species diversity and composition) and forest succession (stand age) on arthropod community characteristics (morphotype diversity, abundance, and composition) of four arthropod functional groups. We found that herbivore species richness was directly correlated with tree species richness. In contrast, detritivore species richness and composition was associated with stand age. Our results suggest that arthropod diversity in a subtropical forest reflects the net outcome of complex interactions among the identity of tree species and the heterogeneity in stand age that alters the spatial structure of the forest.